Bibliometric Analysis on Environmentally Conscious Generation - Judijanto, Loso; Nofirman, Nofirman; Muhtadi, Muhamad Ammar (Westscience Press, 2024)
The growing influence of environmentally conscious generations, particularly Generation Z, has become a pivotal area of research in the context of global sustainability. This study employs bibliometric analysis to systematically map the academic landscape surrounding this field, analyzing keywords, thematic clusters, and temporal trends from scholarly literature published between 2000 and 2023. The findings reveal that sustainability and environmental education are central themes, with strong connections to innovative approaches such as game-based learning and digital advocacy. Generation Z emerges as a key driver of environmental consciousness, leveraging digital platforms to amplify awareness and action. However, the analysis also identifies gaps, including the limited integration of technical solutions, such as renewable energy technologies, with behavioral and educational themes, and a lack of intersectional approaches to examining cultural and socioeconomic influences. This study underscores the need for interdisciplinary collaboration to advance the discourse on environmentally conscious generations and offers a roadmap for future research and practical applications in education, policy, and resource management.